Correction: A quantum chemical study of hydrogen adsorption on carbon-supported palladium clusters. Issue 15 (3rd April 2020) - Warczinski, Lisa; Hättig, Christof
Abstract : Correction for 'A quantum chemical study of hydrogen adsorption on carbon-supported palladium clusters' by Lisa Warczinski et al., Phys. Chem. Chem. Phys., 2019, 21, 21577–21587, DOI: ; 10.1039/c9cp04606b .